Ostergrüsse aus Pakrac
This report outlines the efforts to rebuild the town of Pakrac after the end of the war in Croatia. Pakrac's ethnic composition of Serbs and Croats is outlined, citing how UN officials managed to establish a dialogue between both sides, allowing for some 4,000 refugees to return to their homes. UN Project leader Dr. Michael Platzer is interviewed about the project, emphasizing that mutual distrust must be done away with. He also states the UN's readiness in assisting local people to rebuild their homes and that all that is needed is a firm political agreement allowing refugees to return. The report explains that during the war, Croat forces managed to ethnically cleanse 170 Serb villages in Western Slavonija. In his interview, Veljko Dzakula of the Serbian Regional Counsel, explains that the primary goal is for all people to be able to return to their homes. He further states that war criminals need to be removed out of Pakrac and West Slavonija in general. Finally, a political dialogue needs to be established between all the people living in Pakrac. However, he states, this dialogue must happen outside of the state because there have been no guarantees that Serbs could live safely in Croatia. The report then shows a wedding of Serbs guest workers in Pakrac. Next interviewed is Franjo Sirac, Croat vice-mayor of Pakrac, who explains that Pakrac was a cultural center before the war, and that during the war 90% of the infrastructure was destroyed. He states that it was destroyed by the Serb army who wanted Pakrac to be the capital of the Western Krajina. The report gives a detailed analysis of all the reconstruction going on. Few civilians have the finances necessary to rebuild their homes. The reconstruction of public buildings, such as the local fire station, high school, and train station is financially backed by the UN. Other footage included: destroyed houses and public buildings in Pakrac, pictures of the residents, destroyed hospital rooms, people stacking building blocks, and a destroyed apartment building